Review of the literature - Samoy, Y.; Van Ryssen, B.; Gielen, I.; Walschot, N.; van Bree, H. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
Elbow incongruity is the term to describe bad alignment of the joint surfaces of the elbow. Two features illustrate incongruity of the elbow: an abnormal shape of the ulnar trochlear notch and a step between the radius and ulna, caused by either a short radius or a short ulna. It has been suggested that both an elliptical notch, and a step, can cause increased local pressure within the joint, resulting in loose fragments at different locations: ununited anconeal process (UAP), fragmented coronoid process (FCP), osteochondritis dissecans of the humeral condyle (OCD). These lesions are grouped under the term ‘elbow dysplasia’ and are the most frequent causes of front leg lameness in the dog. Although several radiographic features to diagnose incongruity have been described, the ‘scoring’ of incongruity is subjective because there is currently no objective method to measure the degree of incongruity. Because superimposition is avoided, CT is suggested as a standard technique to measure incongruity. Arthroscopy on the other hand, allows the direct visualisation of the intra-articular structures and their abnormalities. Information on both techniques are still relatively new. Several surgical techniques have been proposed to restore joint congruity; the one most frequently used is an ulnar osteotomy. But because of possible complications, other techniques are being developed. Reports evaluating the results of the different techniques are not yet available.
Keywords: Elbow incongruity; literature; scoring; diagnosis; dysplasia